ANALYSIS OF VISUAL ELEMENTS AND RESPONSES OF GENERATIONS Z ON LAMBORGHINI COMMERCIAL VIDEO - Haingu, Daniel; Yoganandita, I Gede Tangkas; Dewi, Putu Chrisma; Susanto, Putu Chris (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2022)
ABSTRACT Video advertising is a form of advertisement for a product or service that uses video to expand the product. Video advertising is general because it is interesting and memorable for the public. This study aims to analyze one particular advertising media in the form of video used by Lamborghini brand of automobile manufacturer depicting everyday life using visual grammar analysis, and to examine the responses of Indonesian Generation Z on that video using a descriptive qualitative approach. In addition to analysis of visual grammar using the analysis tools by Kress and van Leeuwen, video elicitation interviews were conducted with five participants to further explore the effectiveness of the visual elements from the perspective of Generation Z using the Hierarchy of Effects model of determining advertising effectiveness, paying close attention to the response on the meaningfulness of the visual advertising campaign. Keywords: video advertising, visual elements, generation z, visual grammar, photo elicitation